Contribution of nano crumb-rubber to the rheological characteristics of modified buton rock asphalt - Septiawan, Ahmad; Hadiwardoyo, Sigit Pranowo; Sumabrata, Jachrizal; Lumingkewas, Riana Herlina (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
The increasing number of overloaded vehicles on the highway is one of the factors causing damage to flexible pavements, especially at high temperatures. Therefore, investigating asphalt binders resistant to high temperatures is important. Many studies have been carried out on modifying asphalt with nanomaterials to increase the resistance of asphalt to rutting. One is research using nano crumb-rubber additive material as an asphalt binder variable. This research was carried out with different nano crumb-rubber content of 1.2%, 2.4%, 3.6%, and 4.8% added to pure asphalt binder pen 60/70 and Lawele Bitumen, resulting from extraction from the island of Buton. Rheological tests using the Dynamic Shear Rheometer were used to measure the value of the rutting factor (G*/sin δ) on pure asphalt binder and Asphalt Nano Crumb-Rubber Modified. The asphalt binder resistance to aging conditions can be seen from the aging index value. The results show that adding the percentage of nano crumb rubber to modified asphalt reduces the complex shear modulus (G*) value, the phase angle (δ), and the value of the aging index